Pola Asuh dan Tipe Keluarga dengan Perilaku Seks Bebas Pada Remaja - Putri, Dadya Hadi Nindita; kustin (Jurnal Kesehatan, 2023)
Adolescence is an age in search of identity. One of the most common problems is a decline in moral values ​​because they have not discovered their true identity. The aim of the research is to determine the relationship between parenting style and family type and free sexual behavior in teenagers. The research method is quantitative observational with a cross sectional approach. The population in the research was class XI students of SMK dr. Soebandi numbered 114 respondents with samples taken using simple random sampling. The instrument in the research used a questionnaire on parenting patterns, family type and free sexual behavior with the independent variables parenting style and family type and the dependent variable being free sexual behavior. The research data shows that the distribution of parenting patterns is mostly authoritarian (91.3%), family type is nuclear family (75.4%), and risky sexual behavior (89%). The results of statistical analysis using the Spearman test obtained a p significance value of 0.002, which means there is a relationship between parenting style and free sexual behavior, whereas in both results of statistical analysis the p significance value was 0.745, which means there is no relationship between family type and free sexual behavior in teenagers. . Parenting style and family type are one of the factors that shape adolescent behavior, including sexual behavior. Parental parenting styles shape and support good and bad behavior in teenagers. Keywords: parenting, family type, casual sex behavior, teen